CHALLENGES IN COMBATING CORRUPTION IN NIGERIAN DEMOCRATIC DISPENSATION AND ITS POSSIBLE SOLUTIONS - Mikail, Ibrahim Kawuley; Abdullah, Prof Madya Dr. Mohammad Ainuddin Lee Iskandar (Journal of Techno-Social, 2017)
Corruption is a great disaster that destroys socio-economic development and political prosperity of any nation. In fact, debasement has caused developing countries to fall behind in terms of national and international development. This culminated both state actors and international organisations to wage war against corruption through multiple strategies. The Nigerian fourth republic follows the race in combating corruption and enhancing national development through anti-corruption institutions (EFCC&ICPC) so as to sanitise the political economy of the state. This article elucidates the challenges in combating corruption with aim of offering solutions. Despite the existence of anti-graft institutions, corruption is still going on due to the lack of political will by the government, political interference, lack of autonomy, paucity of funds among others. The qualitative method was duly adopted via in-depth interviews for the purpose of data collection in this study. The study recommends that there is dire need for government political will in combating corruption. Besides that, institutions must become independent with adequate funding in order to meet their target in combating debasement.